Hepatoprotective potential of Tamarindus indica following prenatal aluminum exposure in Wistar rat pups - Helen Ruth Yusuf a , Sunday Abraham Musa a , Abel Nosereme Agbon , Ejike Daniel Eze , Akeem Ayodeji Okesina , Ismail Onanuga , Theophilus Pius , Victor Archibong , Mario Edgar Fernandez Diaz , Juma John Ochieng , Nicholas Kusiima , Bot Yakubu Sunday , Ibe Michael Usman (Elsevier, 2024)
Over time, the use of plant-derived agents in the management of various human health conditions has gained a lot of attention. The study assessed the hepatoprotective potential of ethyl acetate fraction Tamarindus indica leaves (EFTI) during prenatal aluminum chloride exposure. Pregnant rats were divided into 5 groups (n = 4); Group I rats were administered 2 ml kg− 1 of distilled water (negative control), Group II rats received only 200 mg kg− 1 aluminum chloride (positive control), Group III rats were administered 200 mg kg− 1 aluminum chloride and 400 mg kg− 1 EFTI, Group IV rats were administered 200 mg kg− 1 aluminum chloride and 800 mg kg− 1 EFTI, Group V rats were administered 200 mg kg− 1 aluminum chloride and 300 mg kg− 1 Vit E (comparative control). On postnatal day 1, the pups were euthanized, and liver tissues were harvested for the biochemical study (tissue levels of malondialdehyde, caspase-3, tumor necrosis factor-alpha, aspartate aminotransferase, alkaline phos - phatase, and alanine aminotransferases) and the liver histological examination. The administration of EFTI was marked with significant improvement in the tissue levels of malondialdehyde, caspase-3, tumor necrosis factor-alpha, aspartate aminotransferase, alkaline phosphatase, and alanine aminotransferases. There was a marked improvement in histopathological changes associated with prenatal aluminum chloride exposure. In conclusion, the administration of EFTI was protective during prenatal aluminum chloride exposure of the liver in Wistar rats, and is mediated by the anti-lipid peroxidative, antiapoptotic, and anti-inflammatory activity of EFTI.